Relook endoscopy predicts the development of esophageal and antropyloric stenosis better than immediate endoscopy in patients with caustic ingestion - Kochhar, Rakesh; Ashat, Munish; Reddy, Yalaka Rami; Dhaka, Narender; Manrai, Manish; Sinha, Saroj K.; Dutta, Usha; Yadav, Thakur D.; Gupta, Vikas (Endoscopy, 2017)
Background and aims Early ( < 24 hours) esophagogastroduodenoscopy (EGD) is used to prognosticate mucosal injury after caustic ingestion. We aimed to compare differences in endoscopic grading on EGDs performed on day 5 and day 1 and to assess the impact of relook endoscopy findings on the development of esophageal and/or antropyloric cicatrization.Patients and methods Consecutive patients admitted within 24 hours of caustic ingestion between 2009 and 2014 underwent EGD and had their mucosal changes graded. Injuries of grade ≤ 2a were classified as mild and ≥ 2b were classified as severe. Patients were followed up for the development of cicatrization and managed per protocol. Sensitivity, specificity, positive predictive value (PPV), negative predictive value (NPV), and likelihood ratios (LRs) were calculated to compare day 1 and day 5 EGD findings.Results A total of 62 patients (35 men; mean age 33 ± 15) underwent both day 1 and day 5 EGDs. Antropyloric stenosis developed in 16 patients, esophageal strictures in nine, and four had both esophageal and antropyloric strictures. Compared with day 1 EGD, endoscopic grading of severe injury on day 5 had higher specificity (83 % vs. 65 %), higher PPV (60 % vs. 41 %), and higher positive LR (5.65 vs. 2.66) for predicting the development of esophageal stricture. Similarly, day 5 endoscopic grading had higher specificity (95 % vs. 61 %), higher PPV (88 % vs. 54 %), and higher positive LR (16 vs. 2.5) for predicting the development of antropyloric stenosis.Conclusion Endoscopic assessment on day 5 is a better predictor of esophageal and gastric cicatrization than day 1 EGD, which significantly overestimates the grade of injury.